(untitled) (Bangladesh Journal of Agricultural Research, 2012)
An attempt was made to determine the overall farm-specific technical efficiency or inefficiency of onion farms of Bangladesh. Farm-level data were used for the estimation of the parameters of Cobb-Douglas stochastic frontier production function. The model for technical inefficiency effects in the stochastic frontier included age, experience, education, and farm size. The elasticity of output with respect to land, labour, and capital cost was estimated to be positive values of 0.3026, 0.0718, and 0.0442, respectively, and also significant. With respect to seed and irrigation, it was found to be insignificant with negative values of 0.0045 and 0.0007. It indicates that per hectare yield of onion decreases if the amount of seed and irrigation hour increase. The coefficients of age, experience, and farm size were significant with expected negative signs, which means that the inefficiency effects in onion production decreases with increase in age, experience, and farm size. The technical efficiency of onion farms varied from 58% to 99% with mean value of 83%. It denotes that there is a scope to increase output per hectare of onion farm by 17% through the efficient use of production technology without incurring any additional costs. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11191 Bangladesh J. Agril. Res. 37(1): 171-178, March 2012